FOREIGN COUNTRIES’ EXPERIENCE IN THE APPLICATION OF CUSTOMS FEES (International Congress on Economics, Management and Business Studies, 2026)
One of the most important issues today is the accurate determination of customs fees. In setting customs fees, it is essential to take into account protectionism and free trade policies, protect domestic producers from unfair competition, safeguard the rights of consumers, prevent goods from being smuggled into or out of the country, and, finally, effectively utilize factors that contribute to increasing the revenue part of the national budget. To determine the legal nature and precise definition of fees, it is important to identify their relationship with taxes and other types of payments. This issue has been discussed in several legal publications; however, problems still remain in the legal identification of fees. Historically, in different countries, payments with various characteristics have often been referred to by the same term, while, conversely, payments intended to fill the state treasury have been given different names. Thus, terms such as payment, contribution, duty, compensation, and fee each have their own equivalents in different languages.
Keywords: taxes, fees, contributions, and special payments (Sonderabgaben)